Analysis of membrane distillation crystallization system for high salinity brine treatment with zero discharge using Aspen flowsheet simulation - Wang, Rong (2013)
An environmentally friendly membrane distillation crystallization (MDC) system is proposed to treat high salinity reverse osmosis (RO) brine with zero discharge. The raw brine from RO desalination plants is concentrated in direct contact MD to produce pure water, and the concentrate is then crystallized to produce solid salts without secondary disposal. A comprehensive analysis on the MDC system has been performed by Aspen ﬂowsheet simulation with a user customized MD model, which was veriﬁed by our previous experiments. Simulation results reveal that the total energy consumption is negligibly changed by integration of a crystallization unit into the system, as over 97.8% of the energy was consumed by the heater of the MD subsystem. Higher inlet temperatures of both the feed and permeate streams in the MD module can improve the thermal eﬃciency. The introduction of a heat recovery unit in the MDC system, to recover the heat in the permeate for feed preheating, can increase the gain output ratio (GOR) by 28%. Moreover, it is shown that in a hollow ﬁber MD module, the permeate yield is a linear function of the length-to-radius ratio of the membrane module, and a longer MD module can reduce the speciﬁc energy consumption. A relatively high feed ﬂow rate is preferred to avoid the potential problem of crystal blockage in the MD module.